ACCOUNTING STANDARDS FOR FIXED ASSETS OF U.S. GAAP AND IFRS: COVID-19 PANDEMIC AND EARNINGS MANAGEMENT PERSPECTIVES - Andreas Vernando (Berkala Akuntansi dan Keuangan Indonesia, 2021)
FASB and IASB have differences in setting the accounting standard for fixed asset. The FASB does not allow firms to restore the asset value that has been written down, while the IASB allow companies to recover the asset values that has been written down. These differences have distinct implication to depict the COVID-19 pandemic phenomenon and prevent earnings management that will affect the qualitative characteristics of the faithful representation. Therefore, this study aims to analyze the fixed asset accounting standards of U.S. GAAP or IFRS which is more optimal to improve the faithful representation in the case of the COVID-19 pandemic and earnings management. Based on an analysis of the theory and literature review, this study conclude that the fixed assets accounting standard of IFRS is more optimal to represent the COVID-19 pandemic faithfully than that of U.S. GAAP. This is because IFRS allows for recovery of impairment losses. In addition, the fixed asset accounting standard of U.S. GAAP is more optimal than that of IFRS for preventing earnings management so as to improve the quality of faithful representation of the fixed asset value. This is because the fair value measurement for fixed assets involves estimation and subjectivity of the asset appraiser enhancing the possibility of earnings management.